Isopropanol/n -Butanol/Ethanol Separation from Diluted Fermentation Broth by Distillation. Process Optimization using Mixed Integer Linear Programming (MILP) Techniques - Toth, Eszter; Mancino, Gianluca; Raynal, Ludovic (Computer Aided Chemical Engineering, 2022)
This work has been performed in the framework of the development of the bio-based fermentation process to produce IBE (isopropanol/ n-butanol/ethanol). The so-called IBE fermentation is indeed an interesting sustainable alternative to produce fossil-based products. However, product inhibition in fermentation leads to dilute fermentation broths in water (15-25 g IBE/L) which implies high energy demand for products/water separation. In the present study focus has been put on ready-to-industrialize downstream processes for Isopropanol/n-Butanol/Ethanol separation from dilute fermentation broth, using conventional distillation and shell-and-tube heat-exchanger technologies. A reference process scheme, using 5 distillation columns, as well as an IFPEN patented distillation sequence with 3 columns only were optimized using an in-house tool. The tool allows to simultaneously optimize the heat exchanger network configuration and the distillation columns’ operating pressures for a given material balance, using Mixed Integer Linear Programming (MILP) optimization techniques. When comparing to the reference process, the optimized heat exchanger network leads to significant vapor consumption reduction and to also significant total separation cost reduction, when both investments and utilities costs are considered. The IFPEN patented scheme even without optimization is found to be more interesting than the reference scheme and is shown to be even more interesting after optimization. The tool can be applied to any distillation process, leading to significant cost savings.